The Themes of Global Development as a Challenge for Contemporary Education in the Reflection of Future Teachers - Bravena, Noemi; Stara, Jana (Communications - Scientific letters of the University of Zilina, 2018)
The themes of global development should form a significant part of the educational process and also of the so-called turning-to-the child education. The themes include the consequences of globalization, technological development, and the lack of ethical reflection connected with them. The article is divided into a theoretical and an empirical part. The theoretical part is focused on the explanation of the terms still not widely known in the educational process: global citizenship and responsibility, the limits and borders of global development in education, and the way of passing along ambiguous themes. The empirical part presents a concrete lesson on the theme of food waste in the fifth grade of a primary school and its analysis by future teachers, the students of the Faculty of Education at Charles University. The paper is mainly focused on the points which the future teachers considered to be important and which they neglected or “were not able to see.”